Safe surgeries: elaboration and validation of a checklist for outpatient surgical procedures - Thaís Aparecida Porcari; Paula Cristine Figueiredo Cavalari; Alessandra Nazareth Cainé Pereira Roscani; Ana Railka de Souza Oliveira Kumakura; Renata Cristina Gasparino (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Purpose: To prepare and validate the content of a checklist in order to assure the safety for outpatient surgical procedures. Method: Methodological research, performed between May and December 2018, as per three stages: 1) preparation of the checklist; 2) validation of content by five judges; and 3) preliminary testing of the instrument. The concord, among the judges, was measured by the Content Validity Index and the values over 0.9 were considered as being satisfactory. Results: Initially the instrument was prepared having 58 items, considering the heading and six topics. In the first round, two topics and 27 items had an index below 0.9. After reformulations, in the second round, only two items had values below 0.9 and, in the third, all items reached an index of 1.0. Along the preliminary testing, modifications were realized. The final version it has 43 items, distributed as per five topics. Conclusion: The "Checklist for Safe Surgery regarding Ambulatory Surgical Procedures" was prepared and its contents were validated.